Capital Panic - Manchev, Boyan (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Boyan Manchev Title (English): Capital Panic Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 138-141 Page Count: 4 Citation (English): Boyan Manchev, “Capital Panic,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 138-141.